Contributing factors of maize production using multiple linear regressions in mizan-aman district, bench-shako zone, Southwest of Ethiopia - Alemu Bekele Eticha (Open Journal of Plant Science - Peertechz Publications, 2020)
Agriculture is the backbone of the Ethiopian economy. Maize is one of the plants which mostly used for indigenous food like bread, injera, qolo, nifiro and soup in Ethiopia. Despite farmers of Mizan-Aman produce maize, they challenged in a low amount of the production that comes from unknown causes. Therefore, this study was conducted to access the production of smallholder farmers and to identify factors that influence production of maize. The study based on the information which collected from 105 randomly selected farmers, using self-administrative questionnaire. The multiple linear regressions were used and identified factors of maize production. In addition, data diagnostics analysis was used to determine the goodness of the regression model on the maize yield. According to the result, the mean production of maize in study was 33.72 quintal per hectare. Additionally, the regression result revealed that productions of maize were significantly influenced by the education level of producers, fertilizer use, and variety maize seeds that used since each of them have p-value 0.04, 0.000 and 0.042 respectively. Thus, the study suggested, Mizan-Aman developmental agricultural workers must help the maize producer farmers on education level, fertilizer use and seed of maize to improve their production. Furthermore, education level of the farmers will be improved by give training on farming and farming related technologies.